Experimental Study of Integrated Fan Turbine in Oscillating Water Column with Valve System in Venturi Directional and Solar Energy as Hybrid Energy Converter - Madi Madi; Muhammad Gufran Nurendrawan Bangsa; Bintari Citra Kurniawan (WAVE: Jurnal Ilmiah Teknologi Maritim, 2025)
Indonesia, with a maritime area of 7.081.000 km², has significant marine and energy potential. Its vast ocean can generate up to 1995 MW of energy, primarily from strong tidal movements, which can drive turbines to produce electricity. Indonesia's coastal topography supports tidal energy generation, and as a tropical country on the equator, it also has significant solar energy potential, with an average solar irradiation of 217 GWh/year. However, both energy sources are underutilized due to technological challenges, especially in remote areas. Current technologies like Oscillating Water Column (OWC) and Tidal Power Modifier (TPM) are not yet optimal for electricity generation. This experimental model is developed with a flow rectifier system in the venturi tube, which increases the fluid velocity based on continuity theory. Performance evaluation was conducted by recording electrical parameters like voltage and current generated by the turbine and solar PV. Test results showed that the hybrid turbine and solar PV system produced higher electricity output than the turbine without solar energy, with an average electric power of 2.24 x 10 3 watts, and a more optimal hybrid efficiency of 2233.33%.